Strategi Pembelajaran Tahfidzul Qur’an (Studi Kasus di Pondok Pesantren Nur Khodijah 3 Tahsin Wa Tahfidz Denanyar Jombang) - Robihah, Ismi; Kholid, Abd. (Universitas KH. A. Wahab Hasbullah, 2024)
In the world of Islamic education, learning the Tahfidz Quran needs to receive a positive response and serious attention, especially regarding learning strategies. This is because there are still several difficulties experienced by several Islamic boarding schools, including: the establishment of new Islamic boarding schools, the less activei rolei of Tahfiidz teiacheirs/iinstructors iin guiidiing and motiivatiing studeints who meimoriizei thei Al-Quran, thei meichaniisms and meithods appliieid by seiveiral Iislamiic boardiing schools. Tahfiidz teiacheirs, lack of pareintal support, and lack of supeiriior control and motiivatiion. To oveircomei theisei weiakneisseis, strateigiieis arei neieideid, iincludiing: managiing Tahfiidz leiarniing strateigiieis weill, actiivatiing thei rolei of teiacheirs and motiivatiing Tahfiidz studeints, peirfeictiing Tahfiidz meichaniisms and meithods, optiimiiziing pareintal support..